THE DEVELOPMENT HANDOUT Nypa fruticans Wurmb. (Nipah) IN MANGROVE AREA COASTAL OF SUNGAI RASAU AS ENHANCEMENT FOR BIODIVERSITY CONCEPT IN SENIOR HIGH SCHOOL - Riski Maulida; Hardiansyah Hardiansyah; Mahrudin Mahrudin (ATRIUM PENDIDIKAN BIOLOGI, 2021)
Handouts are part of learning resources with all forms of material used to assist educators in carrying out learning activities. The development of locally based teaching materials is carried out to improve student understanding and learning outcomes. One of the environmental uses is to assess the local potential in the school environment. The diversity of plants in the mangrove area is quite large and one of them is Nipah. The research and development aim to analyze the development of the Wurmb Nypa fruticans Handout. (Nipah) in the Sungai Rasau Mangrove Area as an ingredient for enriching biodiversity for high school students. The development model uses Tessmer (1998) to the stage of self-evaluation and expert review. The research and development method used the development steps of the handout, the data analysis of the validity of the Nypa fruticans Wurmb plant handout. by using the validity score formula which includes 3 aspects of feasibility, namely aspects of content feasibility, presentation feasibility and language assessment. The results of the assessment of the validity of the handouts that were developed were stated to be very valid by obtaining an average score on the aspect of content feasibility, namely 91.20%, the average score in the aspect of feasibility of presentation was 95%, and the average score on the aspect of language assessment was 88.46% so that the handouts that have been developed can be used as material for enriching the concept of Biodiversity in SMA.